Major Depressive Disorder and Sleep Disturbance in Patients with Chronic Pain - Patricia C Emery; Keith G Wilson; John Kowal (Pain Research and Management)
BACKGROUND: Disturbed sleep is a common problem in both chronic pain and major depressive disorder (MDD). Moreover, many patients with chronic pain are depressed.